Iron phthalocyanine in non-aqueous medium forming layer-by-layer films: growth mechanism, molecular architecture and applications - Alessio, Priscila [UNESP]; Luz Rodriguez-Mendez, Maria; De Saja Saez, Jose Antonio; Leopoldo Constantino, Carlos Jose [UNESP] (Royal Soc Chemistry, 2010)
The application of organic thin films as transducer elements in electronic devices has been widely exploited, with the electrostatic layer-by-layer (LbL) technique being one of the most powerful tools to produce such films. The conventional LbL method, however, is restricted in many cases to water soluble compounds. Here, an alternative way to produce LbL films containing iron phthalocyanine (FePc) in non-aqueous media (chloroform) is presented. This film fabrication was made possible by exploiting the specific interactions between Fe and NH(2) groups from PAH, poly(allylamine hydrochloride) used as the supporting layer, leading to the formation of bilayers structured as (PAH/FePc)(n). We have also incorporated silver nanoparticles (AgNPs) in LbL films with (PAH/FePc/AgNP)(n) trilayers, making it possible to achieve the surface-enhanced Raman scattering (SERS) phenomenon. The molecular architecture of the LbL films was determined through different techniques. The growth was monitored with UV-Vis absorption spectroscopy, their morphology characterized by optical and scanning electron (SEM) microscopes, and their molecular organization determined using FTIR. The electrochemical properties of the LbL films were successfully applied in detecting dopamine in KCl aqueous solutions at different concentrations using cyclic voltammetry. The results confirmed that the LbL films from FePc in non-aqueous media keep their electroactivity, while showing an interesting electrocatalytic effect. The SERS phenomenon suggested that FePc aggregates might be directly involved in the maintenance of the electroactivity of the LbL films.